2016
DOI: 10.1186/s11671-016-1581-8
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Green Functionalized Cu/Cu2O/ZnO/CuO Nanocomposite for Potential Electrochemical Transducer and Catalyst

Abstract: A novel ternary Punica granatum L-Cu/Cu2O/CuO/ZnO nanocomposite was successfully synthesised via green route. In this work, we demonstrate that the green synthesis of metal oxides is more viable and facile compare to other methods, i.e., physical and chemical routes while presenting a potential electrode for energy applications. The prepared nanocomposite was characterised by both microscopic and spectroscopic techniques. High-resolution scanning electron microscopy (HRSEM) and X-ray diffraction (XRD) techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(41 citation statements)
references
References 41 publications
(44 reference statements)
5
34
0
2
Order By: Relevance
“…Furthermore, broad vibrational stretches were also observed at 2002 cm −1 and 1433 cm −1 which were mainly attributed to the chemisorbed and physisorbed H 2 O and CO 2 molecules on the surface of Cu/Cu 2 O/CuO particles [59,60]. A Similar behaviour was also reported by other researchers [59][60][61]. Compared to the control (peel extract, Fig.…”
Section: Its Frequency Is Indicated Insupporting
confidence: 78%
“…Furthermore, broad vibrational stretches were also observed at 2002 cm −1 and 1433 cm −1 which were mainly attributed to the chemisorbed and physisorbed H 2 O and CO 2 molecules on the surface of Cu/Cu 2 O/CuO particles [59,60]. A Similar behaviour was also reported by other researchers [59][60][61]. Compared to the control (peel extract, Fig.…”
Section: Its Frequency Is Indicated Insupporting
confidence: 78%
“…Thus, it is plausible to conclude that raising the calcination temperatures from 500 °C to 600 °C simultaneously eliminates the strong OH -and the already rather weak -C=O absorptions, suggesting thermally stable and pure Cu/Cu 2 O/CuO/ZnO nanocomposite. The results are in agreement with our previous FTIR results [31]. The DSC measurements of the prepared Cu/Cu 2 O/ CuO/ZnO nanocomposite were also investigated at different calcination temperatures, Fig.3 (a-e).…”
Section: Stability and Crystallinity (Dsc And Tga)supporting
confidence: 81%
“…A large exothermic peak at 330 °C ( Fig.3 (d) peak 2) exhibits the poly-crystallization of Cu/Cu 2 O/CuO/ZnO nanocomposite. Therefore, the DSC measurements proved the poly-crystallization of Cu/Cu 2 O/CuO/ZnO nanocomposite occurred at temperatures over 350 0 C which is in agreement with the data acquired from both SEAD and XRD measurements [31]. …”
Section: Stability and Crystallinity (Dsc And Tga)supporting
confidence: 75%
“…The color changes arise from the excitation of surface plasmon vibrations with the zinc oxide nanoparticles. It was observed that the absorbance peak was centered near 382 nm, indicating the reduction of zinc nitrate hexahydrate into ZnO-NPs [17][18][19].…”
Section: Uv-visible Analysismentioning
confidence: 99%